Enhanced Mitogenic Activity of Recombinant Human Vascular Endothelial Growth Factor VEGF121 Expressed in E. coli Origami B (DE3) with Molecular Chaperones - Kaplan, Ondřej; Zárubová, Jana; Mikulová, Barbora; Filová, Elena; Bártová, Jiřina; Bačáková, Lucie; Brynda, Eduard (PLOS ONE, 2016)
We describe the production of a highly-active mutant VEGF variant, α2-PI1-8-VEGF121, which contains a substrate sequence for factor XIIIa at the aminoterminus designed for incorporation into a fibrin gel. The α2-PI1-8-VEGF121 gene was synthesized, cloned into a pET-32a(+) vector and expressed in Escherichia coli Origami B (DE3) host cells. To increase the protein folding and the solubility, the resulting thioredoxin-α2-PI1-8-VEGF121 fusion protein was co-expressed with recombinant molecular chaperones GroES/EL encoded by independent plasmid pGro7. The fusion protein was purified from the soluble fraction of cytoplasmic proteins using affinity chromatography. After cleavage of the thioredoxin fusion part with thrombin, the target protein was purified by a second round of affinity chromatography. The yield of purified α2-PI1-8-VEGF121 was 1.4 mg per liter of the cell culture. The α2-PI1-8-VEGF121 expressed in this work increased the proliferation of endothelial cells 3.9–8.7 times in comparison with commercially-available recombinant VEGF121. This very high mitogenic activity may be caused by co-expression of the growth factor with molecular chaperones not previously used in VEGF production. At the same time, α2-PI1-8-VEGF121 did not elicit considerable inflammatory activation of human endothelial HUVEC cells and human monocyte-like THP-1 cells.